Analisis Besar Medan Magnet Solenoida Menggunakan Simulasi Virtual Laboratorium Explerify - Syahida Arifatul Jannah; Adam Malik (Universitas Nurul Huda, 2025)
This study aims to analyze the magnitude of the magnetic field in a solenoid using the Explerify virtual laboratory simulation. The study was conducted with a quantitative approach by varying the number of turns (N) and electric current (I), while the coil radius (r) was kept constant at 0.015 m. The simulation results show that the magnetic field increases linearly with increasing number of turns, in accordance with Ampère's Law theory. Comparison between the simulation results and theoretical calculations shows an average difference of around 11–12%. This difference is thought to be caused by parameter limitations in the simulator, especially the length of the solenoid (L), as well as the influence of end effects that are not taken into account in ideal theoretical calculations. Thus, the results of this study indicate that the Explerify virtual laboratory can be an effective alternative for quantitative analysis.